1970
DOI: 10.25081/josac.2019.v28.i2.6074
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of fungal endophytes of black pepper (Piper nigrum L.) and their seed transmission studies

Abstract: The present study envisaged to document the endophytic fungal association with black pepper through a series of in vitro and in planta investigations. Black pepper was found to harbour endophytic fungal flora belonging to the genera Alternaria, Acremonium, Aspergillus, Cladosporium, Chaetomium, Curvularia, Colletotrichum, Fusarium, Humicola, Paecilomyces, Rhizoctonia, Phoma and non-sporulating forms. Further, it was found that the endocarp of black pepper seed is free from culturable endophytic fungi. This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Similarly, Mandlaa et al (2019) et al, 2000). However, Sreeja et al (2019) reported that the endocarp of black pepper seed is free from fungal endophytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Mandlaa et al (2019) et al, 2000). However, Sreeja et al (2019) reported that the endocarp of black pepper seed is free from fungal endophytes.…”
Section: Discussionmentioning
confidence: 99%
“…was recovered from Amaranthus hybridus seeds ( Blodjett et al, 2000 ). However, Sreeja et al (2019) reported that the endocarp of black pepper seed is free from fungal endophytes.…”
Section: Discussionmentioning
confidence: 99%
“…Competition, antibiosis, and mycoparasitism may be some of the disease suppressing features of antagonists. [16][17][18][19] *Mean (± SD) of four replications (n=60). Values in a column followed by the same alphabet do not differ significantly (p≤0.05).…”
Section: Discussionmentioning
confidence: 99%
“…suggested that the different pharmacological results of plants grown aseptically and those grown naturally are possibly due to the effect of the presence of endophytic fungi, in which they affected the production of bioactive metabolites [10] . The leaves, fruits, particularly roots of P. nigrum are likely to be sources of fungal genera such as Fusarium and Penicillium [11,12] . Endophytic fungi normally produce a rich variety of bioactive substances with identical or similar pharmacological activities to those determined from plants [13] .…”
Section: Introductionmentioning
confidence: 99%
“…[10] The leaves, fruits, particularly roots of P. nigrum are likely to be sources of fungal genera such as Fusarium and Penicillium. [11,12] Endophytic fungi normally produce a rich variety of bioactive substances with identical or similar pharmacological activities to those determined from plants. [13] Therefore, it is believed that the fungal endophytes of P. nigrum are likely to produce multiple pharmaceutical properties as similar to the black pepper, especially antimicrobial, antioxidant, anti-inflammatory, antitumor, and antidiabetic.…”
Section: Introductionmentioning
confidence: 99%